Influence of 805 nm Diode Laser on Plasmid Content of Some Locally Isolated Escherichia coli and Proteus Mirabilis - Abdulsattar, Lubna S.; Jawad, Hussein A.; Al-Jubori, Sawsan S. (Iraqi Journal of Laser, 2010)
This work aimed to investigate the effect of Diode laser 805 nm on plasmid DNA and RNAcontents of some Gram negative bacteria represented by Escherichia coli and Proteus mirabilis isolates.Plasmid extraction was done using two methods (Salting out and CTAB method).Different powers andpulse repetition rates for 805 nm Diode Laser were used to study this effect. Results revealed that theplasmid profile of the two species were highly affected using (2, 3) W at different frequencies including5and 10 kHz as compared with 1 kHz while plasmids were gradually disappeared at 1W, 10 kHz. In thesame time the shining of RNA was also decreased gradually then disappeared with increasing powersespecially at 2W and 10 kHz causing disappearing of RNA while using 2 W (1, 5) kHz causes graduallydisappearing. This may suggests using diode Laser as a successful method in plasmid curing.